Memory of past random wave conditions in submarine groundwater discharge. Issue 7 (3rd April 2014) - Xin, Pei; Wang, Shen S. J.; Robinson, Clare; Li, Ling; Wang, You‐Gan; Barry, D. A.
Abstract: Submarine groundwater discharge (SGD) is an integral part of the hydrological cycle and represents an important aspect of land‐ocean interactions. We used a numerical model to simulate flow and salt transport in a nearshore groundwater aquifer under varying wave conditions based on yearlong random wave data sets, including storm surge events. The results showed significant flow asymmetry with rapid response of influxes and retarded response of effluxes across the seabed to the irregular wave conditions. While a storm surge immediately intensified seawater influx to the aquifer, the subsequent return of intruded seawater to the sea, as part of an increased SGD, was gradual. Using functional data analysis, we revealed and quantified retarded, cumulative effects of past wave conditions on SGD including the fresh groundwater and recirculating seawater discharge components. The retardation was characterized well by a gamma distribution function regardless of wave conditions. The relationships between discharge rates and wave parameters were quantifiable by a regression model in a functional form independent of the actual irregular wave conditions. This statistical model provides a useful method for analyzing and predicting SGD from nearshore unconfined aquifers affected by random waves. Key Points: Cumulative effects of antecedent wave conditions on SGD Long memory of past wave conditions back to over a hundred days found in the SGD Wave effects characterized well by a gamma distribution function